Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Sichuan, Southwest China - Tang, Liang; Liu, Sheng-Nan; Dong, Xin-Yu (Zootaxa, 2018)
Seven new species of the Stenus cirrus group collected from Sichuan, Southwest China are described: S. cariniventris Tang, Liu & Dong, sp. n., S. jiangrixini Tang, Liu & Dong, sp. n., S. lineatus Tang, Liu & Dong, sp. n., S. emeishanus Tang, Liu & Dong, sp. n., S. jiudingshanus Tang, Liu & Dong, sp. n., S. xichangensis Tang, Liu & Dong, sp. n., S. brevilineatus Tang, Liu & Dong, sp. n. The diagnostic characters of the new species are illustrated, and a key to species of the group from Sichuan Province is provided.